2013
DOI: 10.1590/s0034-737x2013000400001
|View full text |Cite
|
Sign up to set email alerts
|

Chemical sterilization in in vitro propagation of Arundina bambusifolia Lindl. and Epidendrum ibaguense Kunth

Abstract: RESUMO Esterilização química na propagação in vitro de Arundina bambusifolia Lindl. e Epidendrum ibaguense KunthHá uma grande demanda por técnicas de laboratório mais simples, e de menor custo, e por procedimentos mais acessíveis, por parte de orquidófilos que não têm o embasamento teórico necessário à utilização de métodos usuais de produção, seminífera e clonal, de orquídeas, in vitro. O objetivo deste trabalho foi avaliar a eficiência da aplicação de hipoclorito de sódio (NaClO), para a descontaminação, no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
5
0
2
Order By: Relevance
“…However, prolonged sterilization leads to increase in mortality rate. The negative effect of longer exposure was also reported by many scientists [27,28,29]. Obtaining of uncontaminated explants does not guarantee its establishment.…”
Section: Resultsmentioning
confidence: 83%
“…However, prolonged sterilization leads to increase in mortality rate. The negative effect of longer exposure was also reported by many scientists [27,28,29]. Obtaining of uncontaminated explants does not guarantee its establishment.…”
Section: Resultsmentioning
confidence: 83%
“…The treatment with 4.2 g L -1 of NaClO (143 mL L -1 of CB) for 5 min was, for most species, more effective in controlling contamination, with 87% of germination of the seeds. Rodrigues et al (2013) observed a negative effect on germination with increasing concentration of NaClO, which ranged from 50 to 250 ml L -1 of CB. Such effect was assigned to the disinfectant toxicity.…”
Section: Introductionmentioning
confidence: 91%
“…For the140 mL plastic flasks no significant difference was observed in the proportion of oxidized seeds between the control treatment and the lowest concentration of CB; those with 340 mL, the oxidation was higher ISSN 2166-0379 2017 with the use of CB (Figure 1a). This variation on the seed oxidation is due to, in the case of glass flasks, probably the activated charcoal, which adsorbs toxic compounds, such as phenols, produced by plants, reducing the seeds and the protocorms oxidation (Thomas 2008;Rodrigues et al 2013). In the control treatment, the culture medium was autoclaved inside the flasks and, after its cooling, there was a small decantation of the activated charcoal in the bottom of the flask.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 99%
“…Il a été incorporé au milieu de culture chez le manioc (Hounguè et al, 2017). L'hypochlorite de sodium, largement utilisé en phase de désinfection de surface du matériel végétal (Lopez-Aranda et al, 1994 ;Zuraida et al, 2011 ;Dossoukpèvi et al, 2012) a également été introduit dans le milieu de culture chez certaines espèces (Pierik, 1987 ;Rodrigues et al, 2013). L'ananas, du fait de sa forte teneur en sucre, renferme plusieurs germes rendant difficiles sa désinfection en culture in vitro.…”
Section: Introductionunclassified